Patient‐reported outcome measures of edentulous patients restored with implant‐supported removable and fixed prostheses: A systematic review - Yao, Coral J; Cao, Cong; Bornstein, Michael M.; Mattheos, Nikos (Clinical oral implants research, 2018)
Objective The aim of this systematic review was to compare patient‐reported outcomes measures (PROMs) of implant‐supported fixed complete dentures (IFCDs) and overdentures (IODs). Material and methods PubMed, Cochrane Library, EMBASE, Scopus and Web of Science were searched, complemented by manual search. Studies published in English up to November 2016 comparing removable with fixed implant‐supported prosthesis on fully edentulous patients were included. The review focused on impact on patients’ oral health‐related quality of life (OHRQoL), satisfaction or other patient‐reported outcomes measures. Results Of 1,563 initially screened articles, 13 studies including 8 prospective and 5 retrospective studies fulfilled the inclusion criteria. OHRQoL and patient satisfaction were the most common PROMs. When evaluating the levels of evidence, five of thirteen studies were graded as level III and seven reached level II. The only randomized control trial was rated as Ib. The methods used to evaluate PROMs were heterogeneous among studies, and there was a lack of standardization in the measurements employed. In general, IFCD and IOD showed no significant differences when compared for PROMs, with a slight trend of IFCD being superior to IOD in most included studies. However, conflicting results were observed in many aspects such as chewing function, phonetics‐related function, overall satisfaction and aesthetics. Conclusions Inconsistent results were observed in PROMs when comparing IFCD and IOD for fully edentulous patients. A guideline for standardizing the assessment of PROMs in clinical research is needed in order to produce more meaningful evidence‐based information.